Update on the molecular pathogenesis and clinical treatment of mantle cell lymphoma: report of the 11th annual conference of the European Mantle Cell Lymphoma Network. Issue 4 (April 2013) - Dreyling, Martin; Kluin-Nelemans, Hanneke C.; Beà, Sílvia; Klapper, Wolfram; Vogt, Niclas; Delfau-Larue, Marie-Helene; Hutter, Grit; Cheah, Chan; Chiappella, Annalisa; Cortelazzo, Sergio; Pott, Christiane; Hess, Georg; et al.
Abstract Mantle cell lymphoma (MCL) is a distinct subtype of malignant lymphoma characterized by the chromosomal translocation t(11;14)(q13;q32), resulting in constitutional overexpression of cyclin D1 and cell cycle dysregulation in virtually all cases. Clinically, MCL displays an aggressive course, with a continuous relapse pattern and a median survival of only 3–7 years. However, a subset of up to 15% long-term survivors has recently been identified with a rather indolent clinical course. In general, conventional chemotherapy is only palliative and the median duration of remissions is only 1–2 years. In 2000, the European MCL Network (http://www.european-mcl.net) was founded, which consists of 15 national lymphoma study groups supplemented by experts in hematopathology, cytogenetics and molecular genetics. During the last decade, the European consortium has successfully initiated the largest phase III trials in MCL worldwide. In the current study generation, the addition of high dose cytosine arabinoside (Ara-C) to an R-CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, prednisone)-like regimen followed by myeloablative consolidation achieved a significant improvement of progression-free survival. Similarly, in elderly patients, rituximab maintenance until progression led to a marked prolongation of remission duration. Emerging strategies include proteasome inhibitors, immune modulatory drugs (IMiDs), mammalian target of rapamycin (mTOR) inhibitors and others, all based on the dysregulated cell cycle machinery and impairment of several signaling transduction and apoptotic pathways. Future strategies will apply individualized approaches according to the molecular risk profile of the patient. At the annual conference in Lisbon, recent results of molecular pathogenesis, analyses of current clinical trials and new study concepts were discussed.